THE MANDALIKA SEZ: A PLS-SEM ANALYSIS OF ITS IMPACTS ON REGIONAL ECONOMY AND SUSTAINABILITY DETERMINANTS - Firmansyah, M.; Ro'is, Ihsan; Purwadinata, Subhan; Purnama, Isnan; Hustin, Yunia Yunara (Fakultas Ekonomi dan Bisnis Universitas Tanjungpura, 2025)
Special Economic Zones (SEZs) are policy tools designed to stimulate regional economic growth through investment attraction, industrial development, and employment generation. However, their real impact and sustainability remain subject to debate. In Indonesia, the Mandalika tourism-driven SEZ in Lombok was set to stimulate regional development. This study examines the impact of the Mandalika SEZ on regional economic development and key factors influencing its sustainability from an institutional economic perspective. The variables include economies of scale, urban economy, economic localization, and the SEZ itself. Using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, data were collected from 109 respondents in West Nusa Tenggara. The findings indicate that while SEZ alone has limited influence on economic development, factors like economies of scale, urban economy, and localization contribute more significantly. As for the SEZ’s sustainability, regional economic development is a key determinant. These findings suggest strengthening integration strategies to ensure the long-term success and resilience of a SEZ project like the Mandalika. JEL: L83, O43, Q56.